The Effect of Stress Control and Expectation on Satisfaction with Teacher Colleagues in MTsN (Islamic Junior High School) Stabat, Langkat Regency, Indonesia - Nurmaisari Nasution; Tien Rafida (BIRCU, 2019)
This paper deals with The Effect of Stress Control and Expectation on Satisfaction with Teacher Colleagues in MTsN (Islamic Junior High School) Stabat, Langkat Regency, Indonesia. The conditions that are not conducive where among the teachers there are still those who do not agree to carry out work on the decisions that have been determined are always pros and cons. This research is quantitative research, a type of correlation research using descriptive and inferential approaches and by classifying independent variables and dependent variables. The result shows that there is a moderate tendency in stress control variables, expectation variables and satisfaction variables with teacher colleagues tend to be less. In other words, stress control and expectation together can increase satisfaction with teacher colleagues.